Coccidiae detection in asymptomatic children by esporulation of fecal samples - HUIZA, ALINA (2004)
Objective: To estimate intestinal coccidiae infection prevalence of in asymptomatic children from a marginal community in Lima. Material and Methods: Stool samples were collected from 79 asymptomatic children aged 7 months through 7 year-old from Asentamiento Humano “Las Casuarinas de Villa”. Direct smear and colored frotis by Kinyoun technique were prepared. Another portion was placed in small bottles with potasium bicromatum 2,5% to obtain sporulation. After 10 days, frotis were colored by Kinyoun. Results: Direct smear detected one sample with Cryptosporidium (1,3%). In frotis colored before sporulation, 3 with Cryptosporidium (3,8%) were found and one with Isospora belli (1,3%); in frotis colored post-sporulation 6 samples with Cryptosporidium (7.59%) were detected and one with Isospora belli. Conclusion: Sporulation increases Cryptosporidium detection.